Genetic Relatedness Among Three Populations Of Housefly Musca Domestica L. Using Rapd-Pcr Marker - S. MALVIYA.; N. BAJPAI; R.R. TEWARI (International Journal of Pharma and Bio Sciences, 2011)
Random Amplified Polymorphic DNA-Polymerase Chain Reaction (RAPD-PCR) technique was used to investigate genetic relatedness among populations of housefly Musca domestica (L.) from three different regions of the district Allahabad i.e. Arail, Allahabad city and Jhunsi which are separated by rivers Yamuna and Ganga respectively, to analyze whether these rivers act as geographical barriers to gene flow among the three populations. Tools For Population Genetic Analysis (TFPGA) software was used to calculate heterozygosity and Nei’s genetic identity. Average heterozygosity ranges from 0.278 to 0.370 showing significant level of genetic variability among these populations. The genetic identity among three populations ranges from 0.467 to 0.694, which reveals that there is a low level of genetic identity reflecting the fact that the rivers appear to act as a barrier to gene flow among these populations.